2009
DOI: 10.2176/nmc.49.185
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Elevated Natriuretic Peptide Levels and Cardiopulmonary Parameters After Subarachnoid Hemorrhage

Abstract: Daily changes in serum concentrations of natriuretic peptides and various cardiopulmonary parameters were measured after the onset of subarachnoid hemorrhage (SAH) to investigate the pathogenesis of the cardiac and pulmonary consequences in 15 patients with acute phase SAH, divided into the control group (n = 5) with consciousness continuously preserved from SAH onset to admission, and the consciousness disturbance group (n = 10). Daily changes in serum A-type and B-type natriuretic peptides (ANP and BNP, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Earlier studies have indicated that brain ischemia is associated with the increase of BNP. 13,19,20,22 Nakamura et al 15 described that BNP is higher in unconscious SAH patients than in awake patients. Brain ischemia appears several days after the bleeding as delayed ischemic neurological deficits, which could be associated with the BNP increase.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indicated that brain ischemia is associated with the increase of BNP. 13,19,20,22 Nakamura et al 15 described that BNP is higher in unconscious SAH patients than in awake patients. Brain ischemia appears several days after the bleeding as delayed ischemic neurological deficits, which could be associated with the BNP increase.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant association of MR-proANP serum concentrations with poor outcome and mortality in SAH and ICH patients. Natriuretic peptides have been shown to be elevated in patients with SAH and have been found to be associated with a decreased level of consciousness [17,18]. Data from experimental studies suggest that cerebral ischemia induces ANP release [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al reported a positive correlation between BNP and pulmonary extravascular water content in SAH patients with consciousness disturbance (22).…”
Section: Resultsmentioning
confidence: 99%